The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/ddi.13700
|View full text |Cite
|
Sign up to set email alerts
|

Severe wildfires promoted by climate change negatively impact forest amphibian metacommunities

Abstract: Aim: Changes to the extent and severity of wildfires driven by anthropogenic climate change are predicted to have compounding negative consequences for ecological communities. While there is evidence that severe weather events like drought impact amphibian communities, the effects of wildfire on such communities are not well understood. The impact of wildfire on amphibian communities and species is likely to vary, owing to the diversity of their life-history traits. However, no previous research has identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 128 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, Beranek et al (2023) found that amphibian metacommunities in the southern regions of NSW were negatively impacted by high fire severity, whereas an effect was not detected in the northern region. cracks or within reeds such as Lomandra spp.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, Beranek et al (2023) found that amphibian metacommunities in the southern regions of NSW were negatively impacted by high fire severity, whereas an effect was not detected in the northern region. cracks or within reeds such as Lomandra spp.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, rangerestricted species that occur in remote areas are less well sampled via the FrogID project and other citizen science projects. Other survey methods, such as targeted scientific surveys or passive acoustic monitoring (Beranek et al 2023), may be necessary to elucidate the effects of fire on these species. This may explain why, despite considerable data collection, there were still relatively few sites with high fire impact (n = 11; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to the ability of frogs to seek refuge from the fires (Rowley et al, 2020) and is consistent with our finding of no clear change in frog diversity post-fire in burnt regions compared to before fire or unburnt regions. This does not, however, discount more localized or species-specific impacts of these fires on frogs (e.g., Beranek et al, 2023). Adaptations and behaviors which facilitate fire survival across taxon groupings may reduce immediate mortality and support persistence; potentially alleviating immediate declines in diversity, but this does not necessarily translate to longer term persistence in post-fire landscapes.…”
Section: Adaptations To Fire and The Impacts Of Changing Fire Regimesmentioning
confidence: 98%
“…Trees provide microhabitats that can buffer amphibians from extreme weather events (Scheffers et al, 2013(Scheffers et al, , 2014. For example, tree hollow use is speculated to explain the absence of fire impacts for arboreal amphibian species during climate change-driven fires (Beranek et al, 2023). It is possible that trees provide a refuge for L. aurea from floods.…”
Section: Protection From Extreme Weather Eventsmentioning
confidence: 99%